AB0892 Progressive clinical benefit in chronic refractory gout patients achieving a persistent urate lowering effect from pegloticase treatment. (15th June 2017) - Khanna, P; Mandell, B; Fleischmann, R; Kay, J; Yeo, A; Lipsky, P
Abstract : Background: Pegloticase is a recombinant uricase conjugated to polyethylene glycol approved for treatment of patients with chronic refractory gout. It profoundly decreases serum uric acid (UA) and resolves tophi, but the quality of the clinical benefit in patients achieving long-term UA lowering has not been assessed. Objectives: To assess the clinical benefit of long-term UA-lowering with pegloticase in patients with gout. Methods: This analysis used results from two randomized controlled trials (RCTs) of 6- months duration and the 2-year open-label extension (OLE) of these studies. 1, 2 Efficacy was assessed in responders to the approved treatment regimen (8 mg pegloticase every 2 weeks [q2w]) in the RCTs (i.e., patients with plasma UA <6.0 mg/dL for ≥80% of the assessments around the 3 and 6 month time periods.) Clinical assessments included serum UA, frequency of gout flares, Patient Global Assessment (PGA), tender and swollen joints (TJC and SJC), pain measured with a 100-mm visual analog scale (VAS), Health Assessment Questionnaire Disability Index, bodily pain and the Arthritis-Specific Health Index from the Medical Outcomes Study Short Form 36 item, and reduction of target tophi. Results: 33 patients who responded to pegloticase in the RCTs were followed throughout the OLE. Of these, 20 received 8 mg pegloticase q2w and 13 q4w. Both groups maintained markedly decreased serum UA levels during the OLE. Results for patients who received pegloticase q2w indicated significant improvements between RCT baseline and the final OLE evaluation for serum UA (P<0.0001), PGA (P=0.02), TJC (P=0.04), SJC (P=0.01), and pain VAS (P=0.01); 61.5% of patients in this group had complete target tophus resolution (P<0.0001). Results for those treated q4w indicated significant improvements between RCT baseline and the final OLE evaluation for serum UA (P<0.001), PGA (P=0.004), TJC (P=0.004), SJC (P=0.012), and pain VAS (P=0.01); 100% of patients in this group had complete tophus resolution (P<0.001). After an initial increase in gout flares during the initial 3 months of the RCT, there was a persistent decrease throughout the OLE. Maximal target tophus reduction was observed after 13–25 weeks of the OLE. Two of 20 (10%) patients receiving pegloticase q2w and 4 of 13 (31%) treated q4w lost the persistent UA-lowering effect during the OLE. Conclusions: There were significant sustained clinical benefits with long-term pegloticase treatment in patients with chronic refractory gout achieving a UA lowering effect during the first 6 months of therapy. Significant decreases in TJC, SJC, and pain were noted along with significant improvements in PGA, suppression of gout flares, and resolution of tophi. In most patients, maximal benefit was noted after 6–12 months of pegloticase therapy, with many patients meeting newly proposed criteria for gout remission. 3 References: Sundy JS, et al. JAMA. 2011;306:711–720. Becker MA, et al. Ann Rheum Dis. 2013;72:1469–1474. de Lautour H, et al. Arthritis Care Res. 2016;68:667–672. Disclosure of Interest: P. Khanna Grant/research support from: AstraZeneca, Consultant for: Horizon, Ironwood, Selecta Bio, B. Mandell Grant/research support from: Horizon, Consultant for: Horizon, Ironwood, R. Fleischmann Consultant for: Horizon, J. Kay: None declared, A. Yeo Consultant for: Horizon Pharma, P. Lipsky Consultant for: AstraZeneca, Celgene, EMD Serono, GSK, Horizon Pharma, Janssen, Medimmune, Pfizer, Roche, Sanofi, UCB